Assessing service quality in schools of business: dimensions of service quality in continuing professional education (CPE) - Morales, Miguel; Calderón, Luis Felipe (Universidad ESAN. ESAN Ediciones, 2021)
This paper reports the results of a study on service quality in a business school. We examine the concept of service quality with data collected from 205 executive students. The results obtained from applying exploratory factor analysis to our data suggest that the theoretical factor structure consisting of five factors could not be empirically replicated. The empirical factor structure consist of four factors (tangibles faculty administration and reliability-empathy) being reliability-empathy the most important dimension for professional students. Confirmatory factor analysis results provide strong support for the four-dimensional structure of service quality in a business school setting.

Este documento presenta los resultados de un estudio sobre la calidad del servicio en una escuela de negocios. Examinamos el concepto de calidad de servicio con datos recopilados de 205 estudiantes ejecutivos. Los resultados obtenidos al aplicar el análisis factorial exploratorio sugieren que la estructura factorial teórica que consta de cinco factores no podría replicarse empíricamente. La estructura de factores empíricos consta de cuatro factores (tangibles facultad administración y empatía de confiabilidad) siendo la empatía de confiabilidad la dimensión más importante para los estudiantes profesionales. Los resultados del análisis factorial confirmatorio brindan un sólido apoyo a la estructura de calidad de servicio en cuatro dimensiones en una escuela de negocios.
Keywords: Business schools; Client services; Quality; Escuelas de negocios; Servicios al cliente; Measurement; Calidad; Permanent education; Medición; Educación permanente; Research results; Resultados de la investigación; https://purl.org/pe-repo/ocde/ford#5.02.04